2018
DOI: 10.1111/rode.12558
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of education in China: New evidence from the Chinese Cultural Revolution

Abstract: This paper estimates the effect of parental education on children's education by using instruments generated by the Chinese Cultural Revolution, and further explores the mechanisms of this causal relationship. Several important findings stand out from our empirical analyses. We find a larger intergenerational persistence in education for higher level in urban areas but for a lower level of education in rural areas. The main results from instrumental variable estimation show that the nurture effect is larger an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Several studies have investigated the intergenerational transmission of human capital (see Black and Devereux 2011 for a review). Two China-related studies, Meng and Zhao (2016) and Chen et al (2019), found evidence that the negative consequences of the Cultural Revolution passed onto their offspring.…”
Section: F Effect On the Second Generationmentioning
confidence: 99%
“…Several studies have investigated the intergenerational transmission of human capital (see Black and Devereux 2011 for a review). Two China-related studies, Meng and Zhao (2016) and Chen et al (2019), found evidence that the negative consequences of the Cultural Revolution passed onto their offspring.…”
Section: F Effect On the Second Generationmentioning
confidence: 99%
“…Several explanations have been suggested as to why inter-generational mobility in education has worsened while educational attainment has increased. Chen et al (2019) argue that the expansion of education has not sufficiently reached children from disadvantaged backgrounds. Conceivably, the expansion of higher education in particular would have primarily benefited the elites.…”
Section: Intergenerational Mobility In Education Over Timementioning
confidence: 99%
“…Conceivably, the expansion of higher education in particular would have primarily benefited the elites. Chen et al (2019) argue that many children did not meet the requirements for enrolment in higher education establishments.…”
Section: Intergenerational Mobility In Education Over Timementioning
confidence: 99%
“…Several explanations for why relative mobility in education has worsened while educational attainment has increased have been suggested. Chen et al (2019) argue that the expansion of education has not sufficiently reached children from disadvantaged backgrounds. Conceivably, the expansion of higher education in particular would have primarily benefitted the elites.…”
Section: Relative Mobility In Educationmentioning
confidence: 99%
“…Conceivably, the expansion of higher education in particular would have primarily benefitted the elites. Chen et al (2019) argue that many children did not meet the requirements for enrolment in higher education establishments.…”
Section: Relative Mobility In Educationmentioning
confidence: 99%